Newborn Tetanus - Bazán Zender, Carlos Guillermo (1965)
We proceeded to do a review of 362 cases of neonatal tetanus , treated at the Department of Communicable Diseases Children's Hospital of Lima, between the years of 1959 to August 1963. From the clinical history relevant to these patients is inferred that neonatal tetanus in our environment is a serious public health problem , and one of the causes of infant depopulation in the first stage of life. In the period 1959-1963 , of 44,354 admitted to Children's Hospital of Lima , for various diseases , 362 cases were neonatal tetanus , representing an incidence of 8.11 per thousand. At the same time entered the Department of Communicable Diseases 5,831 patients, of which 362 corresponded to neonatal tetanus , or an incidence of 62.08 per thousand. Unlike the high incidence of neonatal tetanus , only 38 cases of tetanus were found child , which represents an incidence of 0.85 per thousand, compared to inpatient population. Of the 362 cases of tetanus neonatorum studied , 198 were male ( 54.69 %) and 164 sex. female ( 45.31 '% ) . Of the 362 cases of tetanus neonatorum , 277 , or the 76.52 % were from urban areas ; and 85 cases in the rural area , or the 23.48 %. In relation to care delivery, 337 cases with a percentage of 93.09 % received empirical attention , while 25 cases received professional care , of which 23 cases ( 6.30% ) were treated at home, and 2 ( 0.61 %) were treated Motherhood in Lima . Of the cases studied, the first clinical symptoms appeared between 59 and 79 days , in 66% of cases.